Optimizing humidifier performance by modifying packing material location and thickness - K. Srithar; R. Venkatesan; M. Rishidev; R. Saravanan (Desalination and Water Treatment)
Humidifiers play a substantial role in evaporative cooling, air conditioning, and desalination process. As of yet, the impact of packing material thickness and position has not been studied, and this study seeks to fill this gap. A counter-flow humidification test rig is developed using cellulose pads varying in thickness (25 mm, 75 mm, 100 mm, and 150 mm) and position (at 425 mm, 310 mm, and 180 mm from the inlet of the air). Air and water flow rates are operational parameters. There is a range of 1.59 to 5.22 kg/min for air and 8.7 to 23.14 kg/min for water. The humidification efficiency is maximised when the air flow rate is kept at its lowest value (1.59 kg/min) and the water flow is at its highest value (23.14 kg/min). The 25 mm of packing material placed at 425 mm from the air inlet yields a high humidification efficiency (99.79%), an outlet velocity of 10.6 m/s, a cooling capacity of 0.04 kW, a specific cooling capacity of 0.20 kWh/kg, a Coefficient of Performance of 0.19, and a minimum pressure drop of 6.85 Pa for the cooling system. An 80-day payback period has been determined.